New Education Policy 2020: A Comparative Study with Special Reference of Existing Policies, 1968 And 1986 - Sheikh, Altaf Ahmad; Kirmani, Owaise Jan; Shahla, Mufti (International Journal of Psychosocial Rehabilitation, 2020)
The destiny of India is being shaped in her classrooms (Kothari Commission1964-65) had stated that the knowledge, skills, and attitudes students learn work as the cornerstone for nation-building. The key factor in a person’s ability to become independent is their education, which also helps them develop self-confidence and self-esteem. Education is a comprehensive process that fosters not only individual progress but also the enlightening development of society and the country. With all of these factors in mind, the Indian government recognizes the urgent need to implement new educational policies that would essentially modify the way that education is provided in the country, with a concentration on making the education system more comprehensive, inclusive, equitable, qualitative and holistic. In this paper the investigator has discussed the origin and vision of these three (NPE-1968, 1986 and NEP 2020) National educational policies and, to compare NEP-2020 with NPE-1986, of India. This study is qualitative in nature. This paper is purely based on secondary data. The data for this study is collected from the draft NPE-1968, 1986, NEP 2020 and from various articles, journals, books and websites.